Enhanced directly-observed treatment short-course for tuberculosis control program in mountain areas of Taiwan - Huang, Yi-Wen; Tsao, Chang-Yao; Chen, Wei-Wen; Yen, Pai-Sheng; Lee, Jen-Jyh; Huang, Sheng-Shiung; Yang, Hao-Jan (The Journal of Infection in Developing Countries, 2019)
Introduction: Directly Observed Treatment Short course (DOTS) is one of the most cost-effective approaches for TB treatment. However, TB incidence rates remain high in the mountain areas of Taiwan. A lay health advisor (LHA) strategy is integrated into DOTS as an Enhanced-DOTS (E-DOTS) to provide trustworthy, culturally-specific services in mountain areas that consider the characteristics of local ethnic groups. Methodology: We recruited two Taiwanese indigenes as LHAs (one for each county) to screen close contacts in five townships of Hualien and Nantou counties from January 1, 2011 to December 31, 2013. Incidence and active finding rates of TB during the E-DOTS periods (2011-2013 for Hualien and 2012-2013 for Nantou) were compared with data when traditional DOTS was implemented (2006-2010 for Hualien and 2006-2011 for Nantou) to evaluate the effectiveness of E-DOTS using the before-and-after study design. Results: Incidence rate in Hualien decreased from 393.3 in 2011 to 235.7 in 2013 per 100,000 population and from 338 in 2012 to 235.5 in 2013 in Nantou mountain area. Furthermore, the active case finding rate increased from 15.42% in 2012 to 27.38% in 2013 as compared to an average of 6.5% for CDC, Taiwan, for the specified years. TB treatment success rates were significantly improved from an average of less than 80% to an average of higher than 90% after E-DOTS was implemented. Conclusions: Our findings highlighted that the use of LHAs in E-DOTS is an effective and applicable strategy for controlling tuberculosis in the mountain areas of Taiwan.